Early exploration of the Aluto geothermal field, Ethiopia (History of discovery well LA-3). (March 2017) - Hochstein, Manfred P.; Oluma, Befekadu; Hole, Hagen
Highlights: Widespread active manifestations found over Aluto and its flanks (>70 km 2 ). Advective flows caused thermal alteration and low (palaeo-) resistivity structures. Two 1.4 km-deep flank wells (85–105 °C) found c.100 mW/m 2 deep heat flux. A palaeo high-T out-flow event (c.140 kyr) was traced by epidote alteration. The 2.2 km-deep, productive (320 °C) well (LA-3) was sited using TG well data. Abstract: The Aluto geothermal prospect, located in the Southern part of the Ethiopian Rift valley, hosts two large areas with thermal manifestations (c. 30–40 km 2 each), one on top of the Aluto volcanic complex with widespread, weak fumarole activity and another thermal area, 10 km to the south, discharging thermal waters at the Northern shore of Lake Langano. A project (ETH/78/007) with the Ethiopian Government, EEC, and UNDP, was signed in 1978 supporting further exploration and drilling of deep exploratory wells. The first well (LA-1), with T of 85 °C at 1.3 km depth, was sited outside the volcanic complex on flat ground, N of Lake Langano. The second well (LA-2), with T of 105 °C at 1.4 km depth, was located near a fumarole in the W foothills of the Aluto dome. Each well encountered shallow, thermal advective outflows from the Aluto reservoir and impermeable basalts in the bottom section with temperature (T) gradients pointing to an elevated deep heat flux (c. 95–100 mW/m 2 ). Rocks from both wells are thermally altered (slight to moderate intensity) and point to mineral alteration T of >150 °C (LA-1) and up to 250 °C (LA-2). The rocks in the upper 500 m exhibit low resistivities of <5 Ω m. The palaeo-T structure in LA-2 can be interpreted as a conductive heating- and cooling cycle lasting over a period of c. 0.14 Ma using a 1-D analysis. The search for the third well site included the Aluto massif area where resistivity surveys had not found a coherent low resistivity structure in the upper 300 m. This led to the exploration of hot ground using >50 m drill holes. The intersection of a pattern of hot ground and fault- controlled, NNE trending steam vents was used to site the LA-3 well. It was drilled in 1983 to 2144 m depth and encountered 320 °C fluids at the bottom – thus becoming the discovery well of the Aluto geothermal project.